Diagnostic and prognostic significance of the prothrombin time/international normalized ratio in sepsis and septic shock - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Brück, Lea Marie; Hoffmann, Ursula; Bertsch, Thomas; Müller, Julian; Weiß, Christel; Akın, Ibrahim; et al. (Clinical and applied thrombosis, hemostasis, 2022)
Objective - The study investigates the diagnostic and prognostic significance of the prothrombin time/international normalized ratio (PT/INR) in patients with sepsis and septic shock. - Background - Sepsis may be complicated by disseminated intravascular coagulation (DIC). While the status of coagulopathy of septic patients is represented within the sepsis-3 definition by assessing the platelet count, less data regarding the prognostic impact of the PT/INR in patients admitted with sepsis and septic shock is available. - Methods - Consecutive patients with sepsis and septic shock from 2019 to 2021 were included. Blood samples were retrieved from day of disease onset (ie, day 0), as well as on day 1, 2, 4, 6 and 9 thereafter. Firstly, the diagnostic value of the PT/INR in comparison to the activated partial thromboplastin time (aPTT) was tested for septic shock compared to sepsis without shock. Secondly, the prognostic value of the PT/INR for 30-day all-cause mortality was tested. Statistical analyses included univariable t-tests, Spearman's correlations, C-statistics, Kaplan-Meier analyses and Cox proportional regression analyses. - Results - 338 patients were included (56% sepsis without shock, 44% septic shock). The overall rate of all-cause mortality at 30 days was 52%. With an area under the curve (AUC) of 0.682 (p= .001) on day 0, the PT/INR revealed moderate discrimination of septic shock and sepsis without shock. Furthermore, PT/ INR was able to discriminate non-survivors and survivors at 30 days (AUC = 0.612; p = .001). Patients with a PT/INR >1.5 had higher rates of 30-day all-cause mortality than patients with lower values (mortality rate 73% vs 48%; log rank p = .001; HR = 2.129; 95% CI 1.494-3.033; p = .001), even after multivariable adjustment (HR = 1.793; 95% CI 1.343-2.392; p = .001). Increased risk of 30-day all-cause mortality was observed irrespective of concomitant thrombocytopenia. - Conclusion - The PT/INR revealed moderate diagnostic accuracy for septic shock but was associated with reliable prognostic accuracy with regard to 30-day all-cause mortality in patients admitted with sepsis and septic shock.
Online erstmals veröffentlicht: 12. Dezember 2022
Gesehen am 03.06.2024